GETTING THAT SINKING FEELING…. AN UNUSUAL CAUSE OF DEMENTIA. (29th November 2012) - Natalie, S; Wren, D; Isaacs, JD
Abstract : A 58 year old woman with no medical or family history became increasingly apathetic and jovial over several weeks, with a headache lacking postural features. Impaired episodic memory and unsteady gait then developed. Examination revealed a jocular affect, pout reflex, inability to perform the Luria series and mild cerebellar signs. Neuropsychometry showed cognitive slowing, executive dysfunction, impaired registration and recall memory. Brain MRI had a sagging appearance with smooth dural enhancement, suggesting intracranial hypotension. Spinal MRI and CSF were normal other than protein of 0.64 (opening pressure 16). Transient improvement occurred after a first but not second epidural blood patch. Literature review found two similar cases who improved on steroids. Prednisolone 60 mg was trialled with significant subjective improvement. Neuropsychometry showed improved cognitive speed and executive function and the degree of 'brain sag' on MRI improved. Following a 5 month steroid wean she reported complete resolution of symptoms. The term 'frontotemporal brain sagging syndrome', of which this is the first reported British case, has been proposed to describe an FTD-like syndrome associated with 'brain sag' on MRI. The characteristic presentation is thought to be due to disrupted frontotemporal circuits secondary to anatomical distortion of midline structures. However, the mechanisms underpinning both the syndrome and its apparent steroid-responsiveness remain to be elucidated.